Relaksasi Otot Progresif pada Penatalaksanaan Nyeri Pasien Pasca Operasi - Dwi Sudaryanti; Fitria Handayani; Muflihatul Muniroh; Weni Sulastri (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of progressive muscle relaxation interventions in reducing pain levels in postoperative patients. The research method used is scoping review. The results showed that the intervention of progressive muscle relaxation reduced postoperative patients' pain levels. In conclusion, advanced muscle relaxation interventions as non-pharmacological therapy effectively reduce postoperative pain levels. Keywords: Pain, Postoperative, Progressive Relaxation